EMHD stagnation point flow of dusty hybrid nanofluid over a permeable stretching sheet: Radiative solar applications - G. Karthik; P. Vijay Kumar (Case Studies in Thermal Engineering, 2024)
The primary objective of this paper is to investigate the impact of dusty hybrid nanofluid electromagnetohydrodynamics (EMHD) on the stagnation point flow in the presence of solar radiation. Base fluids contain ethylene glycol, water, silver, titanium alloy, and suspended dust particles. Nonlinear differential equations with two or more independent variables define fluid flow phenomena. The governing equations can be solved by the MATLAB solver by employing a suitable numerical method, like R–K fourth order via shooting method. The isothermals for various parametric values have been explained. Because it has the potential to greatly advance the disciplines of industrial and thermal engineering, this proposed model is useful. When compared to using a single base fluid, the combination of two additional base fluid qualities provides noteworthy results. Because we were able to acquire a lower freezing point than water and better heat conductivity than pure ethylene glycol when we employed the combination of the two base fluids. Glycol water is used in car coolant and solar heating systems for a variety of purposes. Impact of embedded physical quantities like electric field parameter, ratio of specific heat, porosity parameter, stagnation parameter, radiation parameter, heat source parameter, and fluid particle interaction parameter for both velocity and temperature are illustrated graphically. Dust particles have a notable impact on various sectors, including the food and pharmaceutical industries. Specifically, they are special importance in applications such as wastewater treatment, solids drying, and the presence of plastic-coated metal items. In the present work, we observe that the stagnation parameter enhances the momentum boundary layer (MBL) thickness because the dusty fluid dominates the dusty hybrid nanofluid while incorporating the Ag + Ti alloy/EG + Water. The radiation becomes more efficient at evenly spreading heat, potentially resulting in a more uniform temperature distribution. Silver and titanium alloy particles may affect the thermal conductivity of dusty hybrid nanofluid when compared to the dusty fluid. The porosity parameter enhances the fluid flow and penetration by the porous medium, which lowers friction between the skin and the surface and reduces resistance.